Gendered economic inequalities: a social policy perspective - Bennett, F (Oxford University Press, 2024)
This commentary addresses gender inequalities from a social policy perspective. It extends the analysis by Andrew et al. in this collection; focuses on lower incomes and social security; and recognizes both individual financial autonomy and interdependence as central. The commentary discusses labour market issues, including how to improve security and in-work progression for women in particular. Policy proposals are also made to limit the disruptions to women’s working lives by care for elderly or disabled people. More broadly, the commentary argues that a key question for any policy is whether it will help transform gender roles and relationships, to allow both sexes to fulfil their capabilities to the full. In addition, both male disadvantage and inequalities and economic dependence within households require more attention. Impact analysis should therefore explore not only distribution between households at the time but also potential effects on individual women and men over the life course. A balance is needed between moves towards economic independence and recognition of past, and continuing, inequalities. Policies can potentially tackle gender inequalities directly, and norms and values that may affect them indirectly. Proposals are put forward for changes in ‘family policy’, including towards second earners, parental leave and childcare. Finally, the commentary argues that the combination of a focus on autonomy and agency for all with awareness of our interdependence as a society and wider world means that gender issues must be central to the Deaton Review, not just for their own sake but also in a broader context.